Ecological and Health Risks Attributed to Rare Earth Elements in Coal Fly Ash - Latinka Slavković-Beškoski; Ljubiša Ignjatović; Mirjana Ćujić; Jelena Vesković; Katarina Trivunac; Jelena Stojaković; Aleksandra Perić-Grujić; Antonije Onjia (Toxics, 2024)
The occurrence and distribution of yttrium and rare earth elements (REYs), along with major elements and heavy metal(loid)s (HMs) in coal fly ash (CFA) from five coal-fired power plants (CFPPs), were analyzed, and the REY-associated ecological and health risks were assessed. The individual REYs in CFA were abundant in the following order: Ce > La > Nd > Y > Pr > Gd > Sm > Dy > Er > Yb > Eu > Ho > Tb > Tm > Lu. The total REY content ranged from 135 to 362 mg/kg, averaging 302 mg/kg. The mean light-to-heavy REY ratio was 4.1, indicating prevalent light REY enrichment in CFA. Significantly positive correlations between the REYs suggested that they coexist and share similar origins in CFA. REYs were estimated to pose low to moderate ecological risks, with risk index (RI) values ranging from 66 to 245. The hazard index (HI) and target cancer risk (TCR) of REYs from CFA, estimated to be higher for children (HIc = 0.15, TCRc = 8.4 × 10−16) than for adults (HIa = 0.017, TCRa = 3.6 × 10−16), were well below the safety limits (HI = 1, TCR = 1.0 × 10−6). However, the danger to human health posed by HMs in the same CFA samples (HIc = 5.74, TCRc = 2.6 × 10−4, TCRa = 1.1 × 10−4) exceeded the safe thresholds (excl. HIa = 0.63). The mean RI and HI attributed to REYs in CFA were 14% and 2.6%, respectively, of the total risks that include HMs.